Comparison of Four Distribution Functions for Fitting Diameter in Second Rotation Tectona grandis Linn. f. Plantations in Eda Forest Reserve, Nigeria (2017)
Tree diameter is a very important variable in forestry; its accurate description is vital to planning if the forest is to be managed in a sustainable manner. Probability density functions are widely used for characterizing tree diameter. However, there is limited information on the diameter distribution for most of plantation in the country especially in the study area. Therefore, this research assesses the performance and suitability of beta, 3-parameter gamma, 3-parameter lognormal and 3-parameter Weibull distribution functions for fitting diameter at breast height (Dbh) of the second rotation of Tectona grandis Linn.F plantation in Eda Forest Reserve, Nigeria. Sixteen (16) temporary sample plots, (each 20 m x 20 m) were randomly selected across four second rotation age series (7, 8, 10 and 11years), whose originalages were 24, 31, 32 and 37 respectively. The distribution functions were fitted using maximum likelihood estimators. The performance of each function was tested using the Kolmogorov-Smirnov (K-S) statistic, Anderson Darling test, Chi-square, mean absolute error (MAE) and mean square error (MSE). The test results revealedthat 3-Parameter Weibull distribution was the most suitable for characterising Dbh. Weibull distribution had the least Kolmogorov-Smirnov statistic (0.0453), Anderson Darling test (1.231), Chi-square (24.9700), mean absolute error (0.0964) and mean square error (2.1688). Therefore, 3-parameter Weibull distribution is the best and recommended for fitting Dbh of second rotation T. grandis species in the study area for sustainable teak timber management.